Halogen substituents enhance oxime nucleophilicity for reactivation of cholinesterases inhibited by nerve agents - Zorbaz, Tamara; Malinak, David; Hofmanova, Tereza; Maraković, Nikola; Žunec, Suzana; Hrvat, Nikolina Maček; Andrys, Rudolf; Psotka, Miroslav; Zandona, Antonio; Svobodova, Jana; Prchal, Lukas; Fingler, Sanja; et al. (European journal of medicinal chemistry, 2022)
The fluorinated bis-pyridinium oximes were designed and synthesized with the aim of increasing their nucleophilicity and potential to reactivate phosphorylated human recombinant acetylcholinesterase (AChE) and human purified plasmatic butyrylcholinesterase (BChE) in relation to chlorinated and non-halogenated oxime analogues. Compared to non-halogenated oximes, halogenated oximes showed lower pKa of the oxime group (fluorinated < chlorinated < non-halogenated) along with higher level of oximate anion formation at the physiological pH, and had a higher binding affinity of both AChE and BChE. The stability tests showed that the fluorinated oximes were stable in water, while in buffered environment di-fluorinated oximes were prone to rapid degradation, which was reflected in their lower reactivation ability. Mono-fluorinated oximes showed comparable reactivation to non-halogenated (except asoxime) and mono-chlorinated oximes in case of AChE inhibited by sarin, cyclosarin, VX, and tabun, but were less efficient than di-chlorinated ones. The same trend was observed in the reactivation of inhibited BChE. The advantage of halogen substituents in the stabilization of oxime in a position optimal for in-line nucleophilic attack were confirmed by extensive molecular modelling of pre-reactivation complexes between the analogue oximes and phosphorylated AChE and BChE. Halogen substitution was shown to provide oximes with additional beneficial properties, e.g., fluorinated oximes gained antioxidative capacity, and moreover, halogens themselves did not increase cytotoxicity of oximes. Finally, the in vivo administration of highly efficient reactivator and the most promising analogue, 3,5-di-chloro-bispyridinium oxime with trimethylene linker, provided significant protection of mice exposed to sarin and cyclosarin.
Keywords: oximy; Nerve Agents; Oximes; Reactivation; organofosforové sloučeniny; Organophosphate; nervová bojová látka; Oxime; Nerve agent; zvířata; Cholinesterase; myši; cholinesterasové inhibitory; Mice; halogeny; sarin; butyrylcholinesterasa; Acetylcholinesterase; reaktivátory cholinesterasy; Organophosphorus Compounds; Halogens; Cholinesterase Reactivators; Sarin; Animals; Butyrylcholinesterase; acetylcholinesterasa; Cholinesterase Inhibitors